KAJIAN POTENSI EKONOMI DI KABUPATEN TANJUNG JABUNG BARAT - Evi Adriani (Universitas Batanghari Jambi, 2015)
Regional economic development involves a multi-sectoral and development actors, so that the necessary cooperation and coordination among all interested parties. Regional economic development is a process in which local governments and communities to manage resources - the resources available and to form a partnership with the private sector to create new jobs and stimulate the development of economic activities in the region. (Arsyad, 1999: 108).Regional development policies that are based on efforts to boost economic growth which can create jobs optimally in terms of quantity, productivity and efficiently determine the success of regional economic development. Policy determination must take into account internal conditions and external developments. Differences in internal and external conditions are just on the coverage region, which covers the internal conditions of the area / region, while the external conditions covering the national territory.Based on the theory of economic base, the main determining factor of economic growth of a region is directly related to the demand for goods and services from outside the area (Arsyad, 1999). Growth industries - industries that use local resources, including labor and raw materials for export will generate local wealth and create jobs (job creation). Implementation of regional development requires planning and a proper strategy because each region has different circumstances, has its own characteristics, economic growth and the potential different.Keyword : economic potential